A Holistic Approach for Teaching Data Structure Course in the Department of Information Technology - Lokare, Varsha T.; Jadhav, Prakash M. (Journal of Engineering Education Transformations, 2025)
A course Data structures have prominent importance for higher studies and placement in software industries. Hence, the better understanding of this course will result in successful career formation. It has been observed that traditional teaching learning methodology is not helping students to showcase their learning's and in turn, it results in poor placement and less success in higher studies. So, in this paper different innovative teaching-learning practices are discussed which help in better understanding of data structure course and which in turn result in good academic development. Finally, the comparative analysis of the course attainment of last two academic years is carried out that result in the noticeable increase in the attainment.